Characteristics of menstrual cycle disorder and saliva metabolomics of young women in a high-temperature environment - Wei, MengFan; An, GaiHong; Fan, LiJun; Chen, XueWei; Li, Chao; Chen, JiaJun; Ma, Qiang; Yang, DanFeng; Wang, Jing (Frontiers in Physiology, 2023)
High-temperature environments induce menstrual disorders, which can seriously damage women's reproductive health and workability. The regulation mechanism underlying the induction of these disorders at high temperature is yet to be elucidated. Saliva is an information-rich biological fluid that can reflect systemic diseases. Here, we investigated the characteristics of menstrual cycle disorders and saliva metabolomics. Women from high and normal temperature areas of China were selected and divided into two groups—high-temperature (H group) and control (C group). A questionnaire survey was conducted in summer (July) to investigate the incidence rate of menstrual disorders, characteristics of the disorders, and factors influencing the risk of these disorders in different regions. Metabolomics was applied to analyze the characteristics of the salivary metabolites and neurotransmitters in the two groups of women with menstrual disorders.The incidence rate of menstrual disorders was significantly higher in the H group than in the C group (P < 0.05). High-temperature environment, pressure, and sleep quality were identified as critical factors associated with menstrual disorders. Non-targeted saliva metabolomics identified 64 significantly different metabolites, which mainly enriched in metabolic pathways such as carbohydrate metabolism, membrane transport, digestive system, and nucleotide metabolism(P < 0.05). Targeted metabolomics of neurotransmitters revealed increased expression of histamine (HA) and glutamine and decreased expression of 5-hydroxyindole acetic acid (5-HIAA) (P < 0.05). Therefore, the incidence rate of menstrual disorder was increased in the H group, which is significantly related to factors such as anxiety, sleep qulity and temperature feeling. Changes in metabolites and neurotransmitters indicated that besides mood, endocrine regulation mechanism, inflammatory reactions that affect the formation of the follicular, cell membrane might contribute to the development of menstrual disorders.